Awareness of Enhanced Recovery after Surgery (ERAS) Protocols among Medical and Nursing Students and Healthcare Professionals in Surgical Departments of Tertiary Level Hospitals in India: A Cross-Sectional Study - Patel, Aditya Raj; Kumari, Ishita; Garg, Hemant Kumar (Journal of Neonatal Surgery, 2025)
Enhanced Recovery after Surgery (ERAS) protocols represent evidence-based perioperative care pathways designed to improve patient recovery after surgery. This study assesses awareness and attitudes toward ERAS protocols among medical and nursing students as well as paramedical staff working in surgical departments of tertiary level hospitals in India. Conducted at the National Institute of Medical Sciences & Research (NIMS&R), Jaipur, Rajasthan, and the Government Institute of Medical Sciences, Greater Noida, Uttar Pradesh, the survey included 100 medical students and interns, 50 nursing students, and 100 paramedical staff (including nurses and technicians). Using a validated structured questionnaire, the study evaluated knowledge, perceptions, and barriers related to ERAS protocol implementation. Results indicate variable awareness levels, with medical students and interns demonstrating higher knowledge compared to nursing students and paramedical staff. The study highlights educational gaps and suggests the need for targeted teaching interventions and institutional support to promote multidisciplinary adoption of ERAS protocols. These findings have implications for improving perioperative care and patient outcomes in tertiary hospitals across India.